2006
DOI: 10.1111/j.1471-4159.2006.04302.x
|View full text |Cite
|
Sign up to set email alerts
|

The same γ‐secretase accounts for the multiple intramembrane cleavages of APP

Abstract: It has been hypothesized that different C-terminus of bamyloid peptide (Ab) may be generated by different c-secretase activities. Recently, we have identified a new f-cleavage site at Ab46, leading to an important finding that the C-terminus of Ab is produced by a series of sequential cleavages. This finding prompted us to examine the effects of the known c-secretase inhibitors on different steps of the c-secretase-mediated sequential cleavages and specifically their effects on the formation and turnover of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 22 publications
3
60
0
1
Order By: Relevance
“…Inconsistency between their results and ours may have arisen from the differences in the assay systems for ␥-secretase; Zhao et al (26) used either cell culture or a cell-free system using the total membrane fraction, whereas we used a cell-free system using the LDM domains. Most importantly, the pH (7.0) of our cell-free system differed from that of the system used by Zhao et al (26) (pH 6.4). We found that A␤ processing at lower pH (pH 6.5) proceeds in a ␥-secretase-independent manner by another protease, presumably involving cathepsin D, whose activity localized to fraction 4.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Inconsistency between their results and ours may have arisen from the differences in the assay systems for ␥-secretase; Zhao et al (26) used either cell culture or a cell-free system using the total membrane fraction, whereas we used a cell-free system using the LDM domains. Most importantly, the pH (7.0) of our cell-free system differed from that of the system used by Zhao et al (26) (pH 6.4). We found that A␤ processing at lower pH (pH 6.5) proceeds in a ␥-secretase-independent manner by another protease, presumably involving cathepsin D, whose activity localized to fraction 4.…”
Section: Discussionmentioning
confidence: 56%
“…This again points to the possibility that the A␤42-producing process is separate from the A␤40-producing process. However, Zhao et al (26) recently reported that A␤46 is an intermediate precursor of both A␤40 and A␤42. Inconsistency between their results and ours may have arisen from the differences in the assay systems for ␥-secretase; Zhao et al (26) used either cell culture or a cell-free system using the total membrane fraction, whereas we used a cell-free system using the LDM domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We extended these findings to ␥-secretase in brains of Tg2576 mice to which 1996; Blanchard et al, 1997;Kim et al, 1997;Siman and Salidas, 2004 belong to the azepinone class of ␥-secretase inhibitors (R. Olson and C. Albright, in preparation). All three of these ␥-secretase inhibitors belong to the nontransition state class of molecules that are proposed to bind to an allosteric binding site on the presenilin subunit of ␥-secretase (Kornilova et al, 2003;Tian et al, 2003;Clarke et al, 2006;Morohashi et al, 2006), and that exert their effect through inhibition of the turnover of ␥-secretase processing intermediates (Qi-Takahara et al, 2005;Zhao et al, 2007 (Yan et al, 2004) and rhesus cortex homogenates (Patel et al, 2006) in the presence of unlabeled ␥-secretase inhibitors indicates that [ 3 H]IN973 is binding specifically to ␥-secretase. Furthermore, previous studies have shown that binding to mouse embryos is greatly reduced in embryos from presenilin-1 knockouts compared with wild-type embryos (Yan et al, 2004 (Iben et al, manuscript in preparation), very similar to the IC 50 values for inhibition of A␤40 in human embryonic kidney cells overexpressing the Swedish mutation of APP of 7.4 and 0.8 nM, respectively, and for inhibition of A␤42 of 7.9 and 0.4 nM, respectively (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…APP family include multifunctional proteins related to Alzheimer's disease, nervous system lesions and epilepsy [17,18] . The three proteins of the APP family (APP, APLP1 and APLP2) share a high degree of similarity in their sequences, but may have different functions [19] , since alterations in ei- ther fragments or protein splicing could lead to various pathological changes [20] .…”
Section: Discussionmentioning
confidence: 99%